Studi Fenomenologi: Pengalaman Kepala Ruangan dalam Melakukan Supervisi pada Perawat di Ruang Rawat Inap COVID-19 - Ruminta Sirait; Bustami Syam; Setiawan Setiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to explore the experience of the head of the room in supervising nurses in the COVID-19 inpatient room. The method used is a qualitative method by determining the sample by purposive sampling. Data was collected through in-depth interviews with several government and private hospitals in Medan City. The results showed that there were five themes regarding the experience of the head of the room in supervising nurses, namely: 1) implementing several approaches to the implementation of the supervisory function of nurses in the COVID-19 inpatient ward; 2) try various efforts to strengthen follow-up supervision; 3) feel the benefits of carrying out supervision of nurses in the COVID-19 inpatient ward; 4) experiencing psychological pressure when supervising nurses in the COVID-19 inpatient room; 5) experiencing problems when carrying out supervision of nurses in the COVID-19 inpatient room. In conclusion, supervision activities can improve the competence, skills, knowledge and manage the performance of nurses in the COVID-19 inpatient room. Keywords: COVID-19, Head of Room, Nurse, Nurse Manager, Supervision, Supervisor